Effectiveness of nurse-led patient-centered care behavioral risk modification on secondary prevention of coronary heart disease: A systematic review. (August 2018) - Chiang, Chung-Yan; Choi, Kai-Chow; Ho, Ka-Ming; Yu, Sau-Fung
Abstract: Background: Despite establishment of advocacies centered on using patient-centered care to improve disease-related behavioral changes and health outcomes, studies have seldom discussed incorporation of patient-centered care concept in the design of secondary cardiac prevention. Objectives: This review aimed to identify, appraise, and examine existing evidence on the effectiveness of nurse-led patient-centered care for secondary cardiac prevention in patients with coronary heart disease. Design: A systematic review of randomized controlled trials focusing on nurse-led patient-centered care for secondary cardiac prevention was conducted. Primary outcomes were behavioral risks (e.g. smoking, physical activity), secondary outcomes were clinically relevant physiological parameters (e.g. body weight, blood pressure, blood glucose, blood lipoproteins), health-related quality of life, mortality, and self efficacy. Data sources: Twenty-three English and seven Chinese electronic databases were searched to identify the trials. Review methods: The studies' eligibility and methodological quality were assessed by two reviewers independently according to the Joanna Briggs Institute guidelines. Statistical heterogeneities of the included studies were assessed by Higgins I2 and quantitative pooling was performed when studies showed sufficient comparability. Results: 15 articles on 12 randomized controlled trials were included in this review. Methodological quality of the included studies was fair. Based on the Joanna Briggs Institute critical appraisal tool for experimental studies, the included studies had met a mean of six criteria out the ten in this appraisal tool. The meta-analyses of the included studies revealed that nurse-led patient-centered care had significantly improved patients' smoking habits, adherence toward physical activity advices, and total cholesterol level with medical regime optimization, in short- to medium-term. The intervention was also favorable in improving the patients' health-related quality of life in several domains of SF-36. Furthermore, from single-study results, the intervention was favorable in improving the patients' weight management and alcohol consumption. However, it did not show significant effects on improving the patient's dietary habits, certain cardiac physiological parameters, mortality and self-efficacy. Currently, no addition long-term benefit of the intervention on secondary cardiac prevention was identified. Conclusion: This review has systematically analyzed the effects of nurse-led patient-centered care on patients' behavioral risks, cardiac physiological parameters, mortality, health-related quality of life and self-efficacy. Given limited quantity of existing evidence regarding certain outcomes and long-term follow-up period; cross-trial heterogeneity of the interventions, measurement methods and statistical results; high or unclear risk of bias in some quality dimensions, the effectiveness of the intervention on secondary cardiac prevention remains inconclusive and subject to additional trials and evidences.